IMPLEMENTASI GOOD CORPORATE GOVERNANCE PADA UNIT PENGENDALIAN GRATIFIKASI di PT PAL INDONESIA (Persero)) - Kumala Sukma Iskandar; Arimurti Kriswibowo (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2023)
The purpose of this research is to find out the review of Good Corporate Governance carried out in carrying out duties at PT PAL Indonesia (Persero). The methodology used in this study is a qualitative descriptive approach, with data collection through observation, interviews, and documentation, with a focus on the five principles of GCG. The results of the study show PT PAL's commitment and seriousness in controlling satisfaction in accordance with GCG principles, applicable laws and regulations, and guidelines to be followed for a healthy business, with an assessment of an increase of 80.4% compared to the previous year.